Константи наукового мислення академіка В.М. Русанівського - Єрмоленко, С. (Культура слова, 2021)
У статті проаналізовано константи наукового стилю
В.М. Русанівського. Праці вченого з граматики, лексикології,
лексикографії, орфографії, історії української літературної
мови, соціолінгвістики, а також філософії мови, теоретичних і практичних питань славістики, репрезентують рівень
розвитку українського мовознавства другої половини ХХ – початку ХХІ ст., засвідчують роль наукового стилю української
літературної мови, зокрема виявляють евристичну цінність
авторських концепцій як констант наукового стилю В.М. Русанівського. До них уналежнюємо такі авторські концепції:
а) репрезентація граматичних категорій дієслова як єдності форми і значення мовної одиниці; б) взаємодія лексичної
і граматичної семантики на всіх рівнях мовної структури;
в) конструктивна взаємодія функціональних і експресивних
стилів в історії літературної мови; г) історія становлення
літературної норми української мови; ґ) розвиток української
літературної мови в контексті системно-структурних, функціонально-комунікативних і екстралінгвальних чинників. Rusanivskyi’s scientific works on grammar, lexicology,
lexicography, spelling, history of Ukrainian literary language,
sociolinguistics, as well as philosophy of language, theoretical and
practical issues of Slavic studies represent the level of development
of Ukrainian linguistics of the second half of XX – early
XXI century.
The overarching idea of the author’s research is the search
for new aspects of language cognition due to the ontological and
epistemological nature of this object. The first studies are devoted
to the history of the Ukrainian language, namely the study of
grammatical categories of type and time in the Ukrainian language
of the XVI – XVII centuries.
In the landmark work “Structure of the Ukrainian verb” on a
large factual material, the researcher traced the structural changes
(variance of the morpheme composition) of verbs in different time
sections of the Ukrainian language.
The most expressive among the constants of the linguist’s
scientific style is attention and constant reference to lexical
semantics, to the meaning of a word in a dictionary and in
specific texts. The author traces and theoretically substantiates the
tendencies of movement in the immanent semantic structure of the
vocabulary of each natural language. It is this tendency that explains
V.M. Rusanivskyi’s constant appeal to the structural-semantic
analysis of T. Shevchenko’s dictionary of language, to the disclosure
of the semantic depth of the word in his texts.
Without claiming a comprehensive analysis of the constants of
Rusanivskyi’s scientific style, we emphasize the heuristic value of
the following authorial concepts: a) representation of grammatical
categories of verbs as the unity of form and meaning of a language
unit; b) the interaction of lexical and grammatical semantics at
all levels of language structure; c) constructive interaction of
functional and expressive styles in the history of literary language;
d) the history of the formation of the literary norm of the Ukrainian
language; e) development of the Ukrainian literary language in
the context of system-structural, functional-communicative and
extralingual factors.